2007
DOI: 10.1063/1.2803071
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast photoluminescence dynamics of nitride-passivated silicon nanocrystals using the variable stripe length technique

Abstract: The ultrafast photoluminescence dynamics of nitride-passivated silicon nanocrystals is investigated using the variable stripe length geometry with 200 femtosecond pump pulses. We find that the luminescence lifetimes are in the nanosecond range throughout the entire spectral range. However, no evidence for optical gain is observed even when the pump fluence is in excess of 40mJ∕cm2. A comparison with similarly prepared, oxide-passivated silicon nanocrystals suggests that oxide passivation plays an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Photoluminescence from nitride-passivated Si-nc has become worthy of attention because of the smaller bandgap than silicon oxide that is in favor of a better carrier injection and thus of more efficient electroluminescence [118,119]. However, despite the fast luminescence decay (ns) and the possibility of tuning the emission in the blue, considerations on the overall luminescence dynamics and the strong optical losses argue against the possibility of obtaining net optical gain [120].…”
Section: Optical Gain In Si Nanocrystalsmentioning
confidence: 99%
“…Photoluminescence from nitride-passivated Si-nc has become worthy of attention because of the smaller bandgap than silicon oxide that is in favor of a better carrier injection and thus of more efficient electroluminescence [118,119]. However, despite the fast luminescence decay (ns) and the possibility of tuning the emission in the blue, considerations on the overall luminescence dynamics and the strong optical losses argue against the possibility of obtaining net optical gain [120].…”
Section: Optical Gain In Si Nanocrystalsmentioning
confidence: 99%
“…Trapped carriers are spatially separated, which may lead to a lower probability of the Auger recombination. 14 Thus, these oxygen-related states may also play a crucial role in the observation of positive optical gain, 15 however, this effect has not yet been fully understood.…”
mentioning
confidence: 99%
“…While Pavesi et al 3 reported that the silicon nanocrystal has a net optical gain, the origin of that gain is considered to be extrinsic, i.e., defects due to the oxide passivation. 7 Therefore, whether intrinsic optical gains by silicon nanostructures are attainable or not is still an unsolved question.…”
mentioning
confidence: 99%